Synthesis and characterization of poly(ester amide) from remewable resources through melt polycondensation - B. B. Wang; Y. P. Ge; D. Yuan; Z. L. Luo (eXPRESS Polymer Letters)
Biodegradable poly(ester amide)s (PEAs) were synthesized from lactic acid and 11-aminoundecanoic acid via melt polycondensation. Molecular weights, chemical structures and thermal properties of the poly(ester amide)s were characterized in terms of gel permeation chromatography (GPC), Fourier transform infrared spectroscopy (FTIR), 1H nuclear magnetic resonance (1H NMR), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA), respectively. The PEAs have low molecular weights and display a lower cold crystallization temperature as well as smaller crystallinity by comparison with the pure poly(lactic acid) (PLA). The incorporation of the 11-aminoundecanoic acid into the PLA chain not only improved the thermal stability but changed the decomposition process.